1986
DOI: 10.1016/0014-5793(86)81134-6
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of a novel intermediate P is involved in the M → bR step of the bacteriorhodopsin photocycle

Abstract: A novel intermediate (P) of the bacteriorhodopsin (bR) photocycle, appearing between M412 and bR is described. Like bR, intermediate P shows an absorption maximum at 56&570 nm. However, the extinction coefficient of P is somewhat lower than that of bR. Moreover, there are some differences in spectra of bR and P at wavelengths shorter than 450 nm. The P+bR transition correlates with the absorption of H+ from the water medium. The following conditions proved to be favourable for the detection of the new intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 2 publications
3
48
0
Order By: Relevance
“…This figure indicates that the amount of N decreases with increasing actinic light density. This is in accordance with the results of Drachev and co-workers [13], and Fig. 5a is a more convincing evidence for this, than obtained from where exponential components were fitted to similar absorption kinetic data.…”
Section: The Kinetics Of the N Intermediatesupporting
confidence: 93%
“…This figure indicates that the amount of N decreases with increasing actinic light density. This is in accordance with the results of Drachev and co-workers [13], and Fig. 5a is a more convincing evidence for this, than obtained from where exponential components were fitted to similar absorption kinetic data.…”
Section: The Kinetics Of the N Intermediatesupporting
confidence: 93%
“…Others have stressed that such multiexponential processes can arise from a single species in equilibrium with other intermediates (8). El-Sayed and coworkers (9) Finally, we propose that R, the very slowly decaying photocycle intermediate (10)(11)(12), may be in a different photocycle than either of those containing the M forms.…”
mentioning
confidence: 63%
“…We assign this difference spectrum to the R intermediate because of its long decay time and its striking similarity with the R spectrum reported earlier (11). Because of the likelihood that the absorption maximum of R is close to that of its parent pigment (11,12), the difference spectrum does not provide a good estimate for the maximum of either the parent pigment or the R intermediate.…”
Section: N4mentioning
confidence: 99%
“…Drachev et al [2] found light-induced absorbance changes which occur more slowly than the disappearance of the M intermediate but synchronous with proton uptake in a suspension of purple membranes. Based on this finding they proposed a new intermediate, P, which follows M and is coupled to proton uptake by bR.…”
Section: Introductionmentioning
confidence: 98%
“…3. Absorption spectra of intermediate N (1) and its bathoform KS (2) in water suspension of purple membrane frozen to -196°C.…”
Section: Introductionmentioning
confidence: 99%